Bridging molecular and cellular neuroscience with proximity labeling technologies - Jun-Gyu Lee; Inyoung Jeong; Kwang-eun Kim (Experimental and Molecular Medicine)
Abstract Proximity labeling (PL) techniques have advanced neuroscience by revealing the molecular interactions that govern neural circuits. From foundational tools such as BioID and APEX to recent innovations such as TurboID and light-activated systems, PL enables precise mapping of protein–protein interactions within living cells. Recent applications have identified dynamic protein networks in synaptic remodeling, calcium-dependent signaling and disease states, such as neurodegenerative and psychiatric disorders. These studies not only deepen our comprehension of the molecular architecture of the brain but also uncover novel therapeutic targets. By integrating PL with cutting-edge multi-omics strategies and advanced imaging technologies, researchers can decode the intricate interplay between structural and functional neural networks. As PL technologies continue to evolve, they bridge molecular and cellular neuroscience, offering a useful framework for unraveling the complexity of brain networks. Here, in this Review, we underscore the potential of PL in neuroscience, furthering our understanding of the molecular basis of neural connectivity in both health and disease.